The Moral Limits of Open‐Mindedness. Issue 4 (29th January 2020) - Ferkany, Matt A.
Abstract : Epistemologists have long worried that the willingness of open‐minded people to reconsider their beliefs in light of new evidence is both a condition of improving their beliefs and a risk factor for losing their grip on what they already know. In this article, Matt Ferkany introduces and attempts to resolve a moral variation of this puzzle: a willingness to engage people whose moral ideas are strange or repugnant (to us) looks like both a condition of broadening our moral horizons, and a risk factor for doing the wrong thing or becoming bad. Ferkany pursues a contractualist line of argument according to which such hazardous engagement is a virtue only when it matters to our interlocutors whether they can justify themselves to us on terms we can accept — for our sake or for the sake of their own virtue, not instrumentally or to get something out of us. When it does not so matter, openness can be unintelligent or gullible — in other words, not virtuous.